Microplankton associations, biofacies and palaeoenvironment of the type lower Ludlow Series, Silurian - Mullins, G; Aldridge, R; Siveter, D (2004)
The acritarchs and prasinophyte algae from the type lower Ludlow Series of the Goggin Road section, Ludlow, England, are resolved into seven recurrent associations comprising taxa with similar environmental preferences. Endemic and environmentally sensitive associations of acritarchs and prasinophytes are identified and high-resolution fluctuations in the early Ludlow palaeoenvironment are established. An early Ludlow crisis in the acritarchs is recognized in the lower part of the Middle Elton Formation, when an abrupt palaeoenvironmental change in the Ludlow area resulted in a large decline in the abundance of the acritarchs, but allowed Tasmanites and retiolitid graptolites to flourish briefly. Cymbosphaeridium sp. A, Pulvinosphaeridium ludlowense and Multiplicisphaeridium arbusculum forma A are taxa possibly specialized, or produced as a response, to a stressed palaeoenvironment, as they are most abundant when other acritarchs and prasinophytes are uncommon. The low abundance of acritarchs and prasinophytes in the Upper Elton Formation may be related to high sedimentation rates and to the slumping of sediments caused by instability on the shelf of the Welsh Basin, or to lower plankton productivity. © 2004 Elsevier B.V. All rights reserved.